2015
DOI: 10.1631/jzus.b1400230
|View full text |Cite
|
Sign up to set email alerts
|

Effect of culturing conditions on the expression of key enzymes in the proteolytic system of Lactobacillus bulgaricus

Abstract: Abstract:The proteolytic system of Lactobacillus bulgaricus breaks down milk proteins into peptides and amino acids, which are essential for the growth of the bacteria. The aim of this study was to determine the expressions of seven key genes in the proteolytic system under different culturing conditions (different phases, initial pH values, temperatures, and nitrogen sources) using real-time polymerase chain reaction (RT-PCR). The transcriptions of the seven genes were reduced by 30-fold on average in the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
(52 reference statements)
0
11
0
Order By: Relevance
“…The highest total amino acid concentration in the sample ( Figure 5A ) might be attributed to the strain hydrolyzed proteins forming the necessary amino acids required for growth ( Hou et al, 2015 ). Amino acids play a key role in enhancing the flavor and increasing the nutrition of the sausages.…”
Section: Discussionmentioning
confidence: 99%
“…The highest total amino acid concentration in the sample ( Figure 5A ) might be attributed to the strain hydrolyzed proteins forming the necessary amino acids required for growth ( Hou et al, 2015 ). Amino acids play a key role in enhancing the flavor and increasing the nutrition of the sausages.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that L. plantarum within its capacity may cause a nitrite response. In addition, Hou, Liu, Ren, Han, and Du () reported several similar observations. Real‐time PCR analysis indicated that the gene expression decreased significantly at the stationary phase compared with the exponential growth phase ( p < .05).…”
Section: Resultsmentioning
confidence: 64%
“…Considerable differences exist in the activity of proteolytic enzymes among different L. bulgaricus. Hou et al (2015) studied the expression of the PepD, PepB, PepC, PepF, PepQ, PepX, and PepT genes in 3 strains of L. bulgaricus under different conditions. The results showed that the protein supply had the least effect on the PepX gene and the strongest effect on OppD (Hou et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Hou et al (2015) studied the expression of the PepD, PepB, PepC, PepF, PepQ, PepX, and PepT genes in 3 strains of L. bulgaricus under different conditions. The results showed that the protein supply had the least effect on the PepX gene and the strongest effect on OppD (Hou et al, 2015). In our study, the sequences of the genes prtB, oppD, pepC, pepF, pepQ, pepX, and pepT, which are key in the proteolysis system, were compared between L. bulgaricus KLDS1.1011 and KLDS1.0207.…”
Section: Discussionmentioning
confidence: 99%